SYSTEM SALES BY MARKET CASH IN MEGA MINI SHOP USING MICROSOFT VISUAL BASIC 6.0 - Harun Al Rasyid; Marzuki Marzuki,Skom.,MMSI (Jurnal Sistem Informasi, 2009)
Sales administration is a tool that can help control financial supervision, the authortries to create a system that would do little to solve problems faced by thesecompanies in this Shop Mega Mini Market, then demanded to strastegi in theprocessing of mini markets to continue running and growing.In making this system penullis using Microsoft Visual Basic 6.0 to get the ease ofprocessing data that changes all the time and the speed and accuracy in thecalculation much more efficient